Clinical heterogeneity of de novo 11q deletion chronic lymphocytic leukaemia: prognostic relevance of extent of 11q deleted nuclei inside leukemic clone. Issue 2 (2nd October 2012) - Marasca, Roberto; Maffei, Rossana; Martinelli, Silvia; Fiorcari, Stefania; Bulgarelli, Jenny; Debbia, Giulia; Rossi, Davide; Rossi, Francesca Maria; Rigolin, Gian Matteo; Martinelli, Sara; Gattei, Valter; Del Poeta, Giovanni; et al.
Abstract Deletion on the long arm of chromosome 11 occurs in 5–20% of chronic lymphocytic leukaemia (CLL) patients. We analysed clinical–biological characteristics of 131 CLL patients carrying 11q deletion documented before therapy (de novo 11q deleted CLL). De novo 11q deleted CLL were characterized by high frequencies of unmutated immunoglobulin variable heavy genes, multiple fluorescence in situ hybridization aberrations and lymph node involvement. Factors significantly associated with shorter time to first treatment (TTFT) were advanced Binet stages, high white blood cell count, increased β2‐microglobulin levels, 17p in addition, splenomegaly and more extensive lymphadenopathy. We found that patients with <25% 11q deleted nuclei (n = 22) experienced longer TTFT compared with patients with ≥25% 11q deleted nuclei (n = 87; median TTFT, 40 vs. 14 months, p = 0.011) and also showed better response to treatments (complete response, 50% vs. 21%, p = 0.016). The variables identified by multivariate analysis as independently associated with reduced TTFT were advanced Binet stages [hazard ratio (HR) 4.69; p < 0.001] and ≥25% 11q deleted nuclei (HR 4.73; p = 0.004). De novo 11q deleted CLLs exhibit variable clinical outcome. The percentage of deleted nuclei inside leukemic clone should be included in the prognostic definition of therapy‐naïve 11q deleted CLL patients. Copyright © 2012 John Wiley & Sons, Ltd.